Cellular development of the germinal epithelium during the gametogenic cycle of the golden mussel Limnoperna fortunei (Bivalvia: Mytilidae) - Dei Tos, Claudenice; Quagio-Grassiotto, Irani [UNESP]; Mazzoni, Talita Sarah [UNESP] (Revista De Biologia Tropical, 2016)
The golden mussel Limnoperna fortunei is an invasive species that has quickly dispersed and colonized several potential different habitats distributed all over the world, causing environmental and economic impacts. Thus, in order to contribute to a better understanding of the reproductive aspects of L. fortunei, we described the cellular dynamic of the male and female germinal epithelium during the annual reproductive life history of this species, with the use of high resolution histology. An approximate of 1 200 specimens of L. fortunei were sampled periodically on the upper Parana River floodplain (Brazil), from March 2010 to December 2012. Based on the activity of the germinal epithelium and consequent germ cell development, this study has resulted in the recognition of the following reproductive phases: Developing, Spawning Capable, Regressing and Regenerating. In the characterization of these phases, the following germ cells were described for males: spermatogonia, primary and secondary spermatocytes, spermatids and spermatozoa. Cell nests, oogonia, early prophase oocytes, previtellogenic oocytes and vitellogenic oocytes (early vitellogenic oocytes, middle vitellogenic oocytes and full-grown oocytes) were described for females. The morphological data and reproductive parameters obtained, showed the value of the cellular dynamics of the germinal epithelium, for the understanding of the cyclic gonadal events during the adult reproductive life of the mollusk in general. These results on the gametogenesis of this invasive species may be a fundamental tool for the development of control strategies and programs implementation, to reduce their proliferation and impacts in natural local environments.
Keywords: Bivalvia; Mytilidae; oogenesis; spermatogenesis; ovary; testis; Limnoperna fortunei